2021
DOI: 10.1136/bmjpo-2021-001036
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 transmissions in students and teachers: seroprevalence follow-up study in a German secondary school in November and December 2020

Abstract: ObjectiveTo quantify the number of undetected SARS-CoV-2 infections in educational settings.DesignSerial SARS-CoV-2 seroprevalence study before and during the second wave of the COVID-19 pandemic.SettingSecondary school in Dresden, Germany.ParticipantsGrade 8–12 students and their teachers were invited to participate in serial blood sampling and SARS-CoV-2 IgG antibody assessment.Main outcome measureSeroprevalence of SARS-CoV-2 antibodies in study population.Results247 students and 55 teachers participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…On one hand, viral culture studies suggest that children may be less infectious than adults 2 , contact tracing studies show low rates of in-school transmission [3][4][5][6][7][8][9][10][11][12][13] , and surveillance studies demonstrate little increased transmission when schools re-opened [14][15][16][17][18][19] . On the other hand, seroprevalence studies have been conducted to account for asymptomatic transmission, but many studies have reported data early in the pandemic, or in the setting of partial school closure 15,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, viral culture studies suggest that children may be less infectious than adults 2 , contact tracing studies show low rates of in-school transmission [3][4][5][6][7][8][9][10][11][12][13] , and surveillance studies demonstrate little increased transmission when schools re-opened [14][15][16][17][18][19] . On the other hand, seroprevalence studies have been conducted to account for asymptomatic transmission, but many studies have reported data early in the pandemic, or in the setting of partial school closure 15,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…We identified 9 studies that reported data on SARS-CoV-2 seroprevalence in educational settings providing in-person activities, 14,15,30,[33][34][35][36][37][38] with a total of 17,879 subjects involved (eTable 2 in the Supplement). All studies were performed in Europe during 2020.…”
Section: Sars-cov-2 Seroprevalence In Educational Settings (Serosurveys)mentioning
confidence: 99%
“…While the above-described point prevalence cross-sectional studies inform on the rates of current infections, cross-sectional serosurveys inform on cumulative exposure to the virus for tested participants. We also identified three cohort studies assessing prevalence of antibodies for SARS-CoV-2 at different time points, with participants tested twice to examine longitudinal changes of seroprevalence, [36][37][38] and we included the most recent testing in our metanalysis. The majority of the studies were judged of high quality (70%, eTable 5).…”
Section: Sars-cov-2 Seroprevalence In Educational Settings (Serosurveys)mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However, major outbreaks of clustered SARS-CoV-2 infections in schools are rare. [7][8][9] Both the specific characteristics of SARS-CoV-2 infection in children (lower viral load and more frequent asymptomatic or mildly symptomatic infections) and the effective mitigation measures taken up by schools, including mask wearing of adults and children, could have contributed to the limited spread in schools. [10][11][12] Despite this uncertainty, numerous countries implemented nationwide school closures to confine the diffusion of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%